Endovascular Treatment of Intracranial Aneurysms with a Branch Arising from the Sac - Lubicz, B.; Lefranc, F.; Levivier, M.; Dewitte, O.; Pirotte, B.; Brotchi, J.; Balériaux, D. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: The endovascular treatment (EVT) of intracranial aneurysms is no more limited by the presence of a branch at the neck or by the neck width. Saccular aneurysms with a branch arising from the sac, however, are mostly candidates for surgery rather than embolization. We prospectively evaluated the feasibility and safety of the EVT in such cases.METHODS: Between May and November 2004, 9 consecutive patients with a saccular aneurysm that presents a branch arising from the sac were treated by embolization. There were 7 women and 2 men (mean age, 58 years). Six patients presented with a subarachnoid hemorrhage (SAH), and 3 were asymptomatic. All patients were treated by selective coiling with (n = 6) or without (n = 3) the remodeling technique. Clinical outcome was assessed with a modified Glasgow Outcome Scale at 3 months.RESULTS: EVT was successfully performed in all patients and resulted in 7 excellent outcomes and 2 deaths related to SAH complications. The arterial branch could be preserved in 7 cases and intentionally occluded in 2. Neither embolic nor ischemic complication occurred in the vascular territory of the involved branch. Angiographic results showed 5 neck remnants, 2 incomplete occlusions, and 2 complete occlusions. No rebleeding occurred.CONCLUSION: Our study, though limited by its small patient population, suggests that saccular intracranial aneurysms with a branch arising from the sac may be treated by endovascular approach with excellent clinical results; however, larger series with long-term follow-up are mandatory to confirm these preliminary results mostly in terms of anatomic stability.